SPINAL DURAL ARTERIOVENOUS FISTULA: CLINICAL CASE AND LITERATURE REVIEW - R. A. Gapeshin; A. A. Yakovlev; A. G. Smochilin; A. V. Gavrichenko; M. S. Pushkaryov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Spinal dural arteriovenous fistula (SDAVF) is a rare disease, however, with nonspecific initial symptoms, like back pain, parestesias, gait imbalance, weakness and numbness in extremities. Para- or tetraparesis, disturbance of deep sensation and pelvic organs functions may develop during the course of disease. There isn’t any specific laboratory tests. So, the diagnostics of dural fistulas is complex. The main screening method is magnetic resonance tomography (MRI), which may suspect or reveal dural fistula. Spinal angiography is a «golden standard» in diagnostics. Options of treatment include microsurgical separation or endovascular embolisation of fistula. The article presents a clinical case of SDAVF in thoracic region of spine. Related to complains, neurological exam and MRI data, the vascular mass was suspected and spinal angiography was per-formed to confirm the presence of SDAVF. After surgical treatment the patient was observed to rehabilitation course, which had improved his status. In sum, appropriate diagnostics, surgical intervention and rehabilitation are the main factors related to successful treatment of patients with SDAVF.